Students’ Difficulties in Reading Comprehension at the Eighth Grade of Islamic Junior High School - Putri, Salmi Ardhani; Abubakar, Multazam; Rauf, Masykur; Rahman, Indah Fadhilah (STAI Nurul Islam Mojokerto, 2025)
The objectives of this research are to investigate the difficulties faced by the students’ and the factors of causing the students’ difficulties in reading comprehension at the eighth grade of MTs Ash-Salihin. This research used mixed methods; research data analysis used quantitative and qualitative methods. The research subjects were thirty-two students. To collect information for this research, researcher used questionnaire and conducted interview. The findings show that students experience difficulties in reading comprehension, including determining main idea, making inference, detail information, and understanding vocabulary. Besides, the factors of causing the students difficulties in reading comprehension are students’ background knowledge, teacher’s technique, and students’ environment. The implications of this research are the teacher need to pay attention to the challenges that students face when they read materials written in English. Teacher can use acceptable, appropriate, and easily understandable teaching strategies for students if they are aware of the many challenges and the variables contributing to them.